Contribution of ginsenosides Rg1, Rb1 to the neuroprotective effect of Panax notoginseng in mouse organotypic hippocampal slice cultures exposed to oxygen and glucose deprivation - Nguyen Thi Thanh Loan; Le Thi Xoan; Pham Thi Nguyet Hang; Nguyen Van Tai (Vietnam Journal of Science, Technology and Engineering, 2021)
We previously demonstrated that Panax notoginseng (pNG) root extract treatments exerted neuroprotective effects on brain injuries using middle cerebral artery occlusion in mice. The present study aims to investigate the neuroprotective effects of PNG extract and its ginsenosides Rg1 and Rb1 on ischemic neuronal damage caused by oxygen and glucose deprivation (OGD) in mouse organotypic hippocampal slice cultures (OHSCs). Before the experiments, hippocampal slices collected from 7-day-old Swiss mice were cultured for 7 days. OGD was triggered in OHSCs for 30, 60, or 90 min with the aim of finding the optimal period of OGD for drug testing. PNG extract (10, 30 µg/ml), ginsenosides Rg1 and Rb1 (5, 25 µM), or MK-801 25 µM, a reference drug, was added to the culture medium 24 h before OGD and these treatments were continued for 24 h after the optimum 60-min period of OGD. After 24 h of OGD exposure, the measurement of propidium iodide uptake was analysed in OHSCs to evaluate neuronal cell damage. The results showed that OGD time-dependently increased PI uptake of the OHSCs. PNG 30 µg/ml treatment reduced the OGD-induced neuronal cell damage in OHSCs. Ginsenosides Rg1 25 µM, Rb1 (5, 25 µM), as well as MK-801 (25 µM) significantly inhibited PI uptake 24 h after OGD exposure. However, ginsenoside Rg1 5 µM did not show any significant effects on the OGD-induced neuronal cell damage. These findings indicated that ginsenosides Rg1 and Rb1 contributed to the neuroprotective effects of PNG against ischemic damage in OHSCs and the neuroprotective effect of ginsenoside Rb1 was stronger than that of ginsenoside Rg1.